1999
DOI: 10.1063/1.124903
|View full text |Cite
|
Sign up to set email alerts
|

Attachment-induced ionization instability of a radio frequency excited discharge in oxygen

Abstract: The plasma of a 13.56 MHz capacitively coupled oxygen discharge of the Gaseous Electronics Conference Reference Cell type exhibits fluctuations of the plasma potential and of light emission in the kilohertz range. This behavior can be explained in terms of an attachment-induced ionization instability in connection with a sufficiently high fraction of negative ions. A necessary condition for the appearance of this type of instability is a strong positive dependence on electron temperature of the electron attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 8 publications
4
25
0
Order By: Relevance
“…As was shown in paper [13], attachment-induced ionisation instability can be excited in the RFcapacitive discharge in oxygen. In the RF discharge in oxygen there are a large number of negative ions O À , whose concentration can be comparable to or even can exceed the concentration of electrons [7,8].…”
Section: Article In Pressmentioning
confidence: 91%
See 2 more Smart Citations
“…As was shown in paper [13], attachment-induced ionisation instability can be excited in the RFcapacitive discharge in oxygen. In the RF discharge in oxygen there are a large number of negative ions O À , whose concentration can be comparable to or even can exceed the concentration of electrons [7,8].…”
Section: Article In Pressmentioning
confidence: 91%
“…The authors of this paper derived the criterion for the onset of this instability in plasma containing negative ions. This criterion was used by the authors of papers [13,24] for elucidating the nature of the instability they had observed in RF-capacitive discharge in oxygen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also presented [16] numerical evidence regarding a new type of self-sustaining mechanism for RF oxygen plasma when new electrons are generated in the bulk plasma by the detachment reaction from negative ions with high density under the condition of a relatively high bulk field. Katch et al [17] found that the plasma of a 13.56 MHz capacitively coupled oxygen discharge of the GEC reference cell exhibits fluctuations of the plasma potential and light emission in the kilohertz range. They explained this behaviour in terms of an attachment-induced ionisation instability in connection with a sufficiently high fraction of negative ions.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of experimental and theoretical papers studying the characteristics of this type of the discharge were published (see, e.g., [6][7][8][9][10][11][12][13][14][15][16][17]). Let us present a brief review of main results obtained with the RF discharge in oxygen.…”
Section: Introductionmentioning
confidence: 99%